Regional differences in diabetes across Europe: Regression and causal forest analyses - Petér S. Elek; Anikó Bíró (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2020)
We examine regional differences in diabetes within Europe, and relate them to variations in socio-economic conditions, comorbidities, health behaviour and diabetes management. Using SHARE (Survey of Health, Ageing and Retirement in Europe) data, first, we estimate multivariate regressions, where the outcome variables are diabetes prevalence, diabetes incidence, and weight loss due to diet as an indicator of management. Second, we study the heterogeneous impact of the risk factors on the regional differences in incidence with causal random forests. Compared to Western Europe, the transition odds to diabetes is 2.3-fold in Southern and 2.7-fold in Eastern Europe, which decreases to 2.0 and 2.1 after adjusting for individual characteristics. The remaining differences are explained by country-specific healthcare indicators. Based on the causal forest approach, the adjusted East-West difference is essentially zero for the lowest risk groups (tertiary education, no hypertension, no overweight) and increases substantially with these risk factors, but the South-West difference is much less heterogeneous. The prevalence of diet-related weight loss around the time of diagnosis also exhibits regional variation. The results suggest that more emphasis should be put on diabetes prevention among high-risk individuals in Eastern Europe.
Keywords: C21; C45; I10; I12; I14; 330; causal forest; diabetes; Europe; health behaviour; SHARE data